2012
DOI: 10.4319/lom.2012.10.590
|View full text |Cite
|
Sign up to set email alerts
|

Intercalibration of selected anthropogenic radionuclides for the GEOTRACES Program

Abstract: As part of the GEOTRACES Program, six laboratories participated in an intercalibration exercise on several anthropogenic radionuclides of interest. The effort was successful for 239,240Pu activity, 240Pu/239Pu isotope ratio, and 137Cs activity measured in filtered seawater samples from the Bermuda Atlantic Time Series station (BATS) and a site on the continental slope of the Northeastern U.S. A limited number of analyses were reported for 237Np, 241Am, 90Sr, and 238Pu in filtered seawater. Intercalibration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…4,53 They were lower than those affected by the Sellafield nuclear fuel reprocessing plant (NRP) discharge such as in the Irish Sea (0.1−1.0 mBq L −1 ), 54 an area near the Sellafield NRP (9 mBq L −1 ), 55 and in the Danish Sea (0.65−1.69 μBq L −1 ), 8 etc., while they were higher than the estimated global deposition values (0.03−0.065 μBq L −1 ) (Table S5). 8,10 Moreover, the 237 Np/ 239 Pu atom ratios (9.0−19.2) were comparable to those in surface waters of the Western Atlantic Ocean (10) and Northwestern Mediterranean Sea (4), which are mainly influenced by global fallout, 4,53 but significantly lower than those of the Danish seawater (24.2−84.8) influenced by the Sellafield NRP discharge. 8 These results indicated that 237 Np in the northwest Pacific Ocean around the FDNPS site mainly originated from global fallout; however, the 240 Pu/ 239 Pu atom ratio (0.178−0.273) as a fingerprint for Pu source identification indicated that Pu in the study area was not only derived from global fallout but also from the Pacific Proving ground (PPG)-Pu input.…”
Section: mentioning
confidence: 96%
See 1 more Smart Citation
“…4,53 They were lower than those affected by the Sellafield nuclear fuel reprocessing plant (NRP) discharge such as in the Irish Sea (0.1−1.0 mBq L −1 ), 54 an area near the Sellafield NRP (9 mBq L −1 ), 55 and in the Danish Sea (0.65−1.69 μBq L −1 ), 8 etc., while they were higher than the estimated global deposition values (0.03−0.065 μBq L −1 ) (Table S5). 8,10 Moreover, the 237 Np/ 239 Pu atom ratios (9.0−19.2) were comparable to those in surface waters of the Western Atlantic Ocean (10) and Northwestern Mediterranean Sea (4), which are mainly influenced by global fallout, 4,53 but significantly lower than those of the Danish seawater (24.2−84.8) influenced by the Sellafield NRP discharge. 8 These results indicated that 237 Np in the northwest Pacific Ocean around the FDNPS site mainly originated from global fallout; however, the 240 Pu/ 239 Pu atom ratio (0.178−0.273) as a fingerprint for Pu source identification indicated that Pu in the study area was not only derived from global fallout but also from the Pacific Proving ground (PPG)-Pu input.…”
Section: mentioning
confidence: 96%
“…These values were consistent with the 237 Np activity concentrations in the Mediterranean (0.14−0.20 μBq L −1 ) and Western Atlantic Ocean (0.07−0.20 μBq L −1 ) that are mainly affected by global fallout. 4,53 They were lower than those affected by the Sellafield nuclear fuel reprocessing plant (NRP) discharge such as in the Irish Sea (0.1−1.0 mBq L −1 ), 54 an area near the Sellafield NRP (9 mBq L −1 ), 55 and in the Danish Sea (0.65−1.69 μBq L −1 ), 8 etc., while they were higher than the estimated global deposition values (0.03−0.065 μBq L −1 ) (Table S5). 8,10 Moreover, the 237 Np/ 239 Pu atom ratios (9.0−19.2) were comparable to those in surface waters of the Western Atlantic Ocean (10) and Northwestern Mediterranean Sea (4), which are mainly influenced by global fallout, 4,53 but significantly lower than those of the Danish seawater (24.2−84.8) influenced by the Sellafield NRP discharge.…”
Section: mentioning
confidence: 96%
“…The programme also includes anthropogenic radionuclides. As part of the programme, intercalibration efforts have demonstrated the ability to identify plutonium-239, plutonium-240 and caesium-137 from relatively small samples (Kenna and others, 2012). Radioisotope data collected through the GEOTRACES programme have also contributed substantially to the understanding of movements of material in the ocean (Malakoff, 2014).…”
Section: Generalmentioning
confidence: 99%